Corrosion behaviour of ferrous and non-ferrous alloys exposed to sulphate - reducing bacteria in industrial heat exchangers - Prithiraj, Alicia (Vaal University of Technology, 2018)
Corrosion responses of some carbon steels, stainless steel and copper alloys in the presence of a culture of bacteria (referred to as SRB-Sulphate-reducing bacteria) found in industrial heat exchangers, was studied to recommend best alloys under this service condition, with techno-economic consideration. Water from cooling towers in three plants in a petrochemical processing complex were analysed for SRB presence. Two of the water samples showed positive indication of SRB presence. The mixed cultures obtained from plant one were grown in prepared media and incubated at 35 °C for 18 days. Potentiodynamic polarisation studies in anaerobic conditions were done on the selected alloys in aqueous media with and without the grown SRB. Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) were then used to study the corrosion morphology and corrosion products formation. The voltamograms show higher icorr for alloys under the SRB compared to the control media, indicating the SRB indeed increased the corrosion rates. The surface analysis showed pitting on steel alloy ASTM A106-B. Localised attack to the grain boundaries on a selective area, was seen on ASTM A516-70 dislodging the grains, and intergranular corrosion was seen throughout the exposed area of ASTM A179. Copper alloys showed pitting on ASTM B111 grade C71500 (70-30), and denickelification on ASTM B111 grade C70600 (90-10), and is a good alternative material for use apart from carbon steel alloys, recording a low corrosion rate of 0.05 mm/year. The EDS analysis supported the findings showing higher weight percent of iron and sulphur on surface of the alloys after exposure to the SRB media. This implies that the presence of the sulphur ion indeed increased the corrosion rate. ASTM A516-70 carbon steel was chosen as a suitable alternative material to the stainless steel in this environment. The Tafel plot recorded a corrosion rate of 1.08 mm/year for ASTM A516-70 when exposed to SRB media.
M.Tech. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology
Keywords: Corrosion behaviour; Sulphate-reducing bacteria (SRB); Cooling tower; Heat exchanger; Carbon steels; Corrosion and anti-corrosives.; Dissertations, Academic -- South Africa; Ferrous oxide; Alloys; Sulfate-reducing bacteria